Single-grain cutting based modeling of abrasive belt wear in cylindrical grinding - Zhe He; Jianyong Li; Yueming Liu; Jiwang Yan (Friction)
Abstract A systematic wear model of the cylindrical grinding process with an alumina abrasive belt from the perspective of single grain sliding wear was established in this study. The model consists of three parts: a single cutting force model derived by applying a stress integration method, a single grain wear height analysis based on the wear rate of alumina, and a grinding mileage prediction of multiple grains with Gaussian distributed protrusion heights. Cutting force, single grain wear height and full-size grinding mileage verification experiments were conducted. The results indicated that the established model was in reasonable agreement with the experimental outcomes, which suggests that this model could be useful in the industry to predict the wear process of abrasive belts.